2021
DOI: 10.3390/ma14102615
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Mediated Rapid and Facile Synthesis of Silver Nanoparticles and Their Antimicrobial Efficacy against Pathogenic Microorganisms

Abstract: In the present study, silver nanoparticles (AgNPs), biosynthesized using culture supernatant of bacterial strain Paenarthrobacter nicotinovorans MAHUQ-43, were characterized and their antimicrobial activity was investigated against both Gram-positive Bacillus cereus and Gram-negative bacteria Pseudomonas aeruginosa. Bacterial-mediated synthesized AgNPs were characterized by UV-Visible (UV-Vis) spectrophotometer, field emission-transmission electron microscopy (FE-TEM), energy dispersive X-ray (EDX), X-ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…MAHUQ-52 mediated synthesized AgNPs against K. pneumoniae and S. Enteritidis were 17.6 ± 0.5 and 16.8 ± 0.9 mm, respectively. These findings are consistent with previous studies that showed the antimicrobial activities of biosynthesized AgNPs against Bacillus cereus and Pseudomonas aeruginosa [ 17 ]. Six standard antibiotic disks, including erythromycin, vancomycin, penicillin, novobiocin, oleandomycin and lincomycin, were also used as a control to check their antibacterial efficacy.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…MAHUQ-52 mediated synthesized AgNPs against K. pneumoniae and S. Enteritidis were 17.6 ± 0.5 and 16.8 ± 0.9 mm, respectively. These findings are consistent with previous studies that showed the antimicrobial activities of biosynthesized AgNPs against Bacillus cereus and Pseudomonas aeruginosa [ 17 ]. Six standard antibiotic disks, including erythromycin, vancomycin, penicillin, novobiocin, oleandomycin and lincomycin, were also used as a control to check their antibacterial efficacy.…”
Section: Resultssupporting
confidence: 93%
“…Bacterial strains of K. pneumoniae and S. Enteritidis (log-phase cells, approximately 1 × 10 7 CFU/mL) were each incubated with and without AgNPs (at MBC concentration) for 12 h at 37 °C. After the incubation period, samples were collected from both cultures and processed for FE-SEM analysis according to the previous description [ 17 ]. Briefly, the overnight-treated cells were centrifuged at 8000 rpm for 5 min, and the supernatant was poured out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses [27], bacteria and actinomycetes [28][29][30], yeasts and fungi [31][32][33], and algae and plants [34][35][36] have been applied for the synthesis of metallic nanoparticles. Due to the diverse set of bioactive constituents presented in plant extracts, the reduction of metal ions or metal oxides, followed by the nucleation and growth of nanoparticles, occurs in solution at room temperature [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a fundamental need to develop clean, environmentally benign, non-toxic, and safe approaches to the preparation of nanomaterials exploiting sustainable and cost-effective technologies. These essential challenges have led researchers to place a focus on biological systems, including bacteria [ 7 ], fungi [ 8 ], algae [ 9 ], and plants [ 10 ]. Considering the cost-effectiveness of the preparation of nanoparticles (NPs), methods based on phytochemical-mediated reduction of metal ions may provide an economic and valuable alternative for the production of NPs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%